Critical thinking : - Gregory Bassham (McGraw-Hill Higher Education, 2010)
This popular text helps today's students bridge the gap between everyday culture and critical thinking. Using a proven step-by-step approach, this text covers all the basics of critical thinking, in clear, reader-friendly language. Its comprehensiveness allows instructors to tailor the material to their individual teaching styles, resulting in an exceptionally versatile text